Incorporation of Benzothiazole and Pyrimidine Moieties on Napthol Platform for Their Sensing Properties - Goyal, Charu (My University, 2018)
Two chemosensors (6-amino-5-(((2-hydroxynaphthalen-1-yl)methylene)amino)-2-mercapto pyrimidin-4 (Probe 1) and 3,3'-bis(benzo[d]thiazol-2-yl)-[1,1'-binaphthalene]-2,2'-diol (Probe 3) were synthesized for Al3+ detection and OCl- detection via fluorometric approaches. Probe 1 displayed shift in absorption spectrum in presence of Cu2+ metal ions from 420 nm to 450 nm. And enhancement in fluorescent spectrophotometer from in presence of Al3+ metal ions from 420 to 520 nm. On the other hand, Probe 3 do not show any change in absorption spectrum on addition of any metal ion. But show enhancement in emission spectrum at 420 nm. Therefore, Probe 1 shows fluorogenic response towards Al3+ metal ion in aqueous methanol medium and Probe 5 shows fluorogenic response towards OCl- ion in aqueous ACN medium. Probe 1 contains benzothiazole unit and probe 3 contains BINOL unit.
Keywords: Benzothiazole; Binol; Chemosensors